Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia - Emery, David L.; Lee, Young June; Pham, Hong-Thai (Zootaxa, 2017)
This paper provides descriptions of four new species of the genus Semia Matsumura, 1917 from Vietnam: Semia magna sp. nov., Semia spiritus sp. nov., Semia pallida sp. nov., and Semia albusequi sp. nov. A key to the 13 species of Semia is provided.